National Bibliographies on the Internet - Petrović, Vera (Infotheca - Journal for Digital Humanities; Vol 5 No Special is (2004): Infotheca - Journal of Informatics and Librarianship, 2024)
On the 69th IFLA Congress Section for Bibliography had a session on Electronic National Bibliographies on the first day.